Synthesis and anti-HCMV activity of novel cyclopropyl phosphonic acid nucleosides - Kim, Aihong; Hong, Joon Hee; Oh, Chang Hyun (TAYLOR & FRANCIS INC, 2006)
A simple synthetic route for novel acyclic phosphonate nucleosides is described. The characteristic cyclopropyl moiety 8 was constructed employing the Simmons-Smith reaction as key step starting from simple acyclic 2-butene-1,4-diol. The condensation of the mesylate 11 with natural nucleosidic bases (A, C, T, U) under nucleophilic substitution conditions (K2CO3, 18-Crown-6, DMF) and hydrolysis afforded the target nucleosides 16, 17, 18, and 19. In addition, the antiviral evaluations against various viruses were performed.
Keywords: ANTIVIRAL ACTIVITY; MITSUNOBU REACTION; ANALOGS; DERIVATIVES; POTENT; AGENTS; VIRUS